2013
DOI: 10.1088/0952-4746/33/4/735
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different phantom designs for CT scanner automatic tube current modulation system tests

Abstract: Modern CT scanners modulate tube current during scans according to patient size, shape and attenuation. However, the ATCM (automatic tube current modulation) systems for different CT manufacturers work on different principles. Although the systems are used for the majority of patients and examinations, there is no standard phantom for routine quality control of CT scanner ATCM operation. The ideal phantom for testing these systems should be capable of evaluating how tube current and image quality as well as do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…5,8,9,18,19 From those studies, it is concluded that an ideal phantom should be applicable to use for the evaluation of longitudinal as well as angular ATCM and provide a means for quantifying image quality. Sookpeng et al 18 have used phantoms with sharp discontinuities and air gaps, concluding that these properties should be avoided. Further, the phantom should have regions with constant geometry wider than the total beam collimation to allow the modulation to stabilize.…”
Section: Phantommentioning
confidence: 99%
“…5,8,9,18,19 From those studies, it is concluded that an ideal phantom should be applicable to use for the evaluation of longitudinal as well as angular ATCM and provide a means for quantifying image quality. Sookpeng et al 18 have used phantoms with sharp discontinuities and air gaps, concluding that these properties should be avoided. Further, the phantom should have regions with constant geometry wider than the total beam collimation to allow the modulation to stabilize.…”
Section: Phantommentioning
confidence: 99%
“…The tube current indicated in Table 4 showed a similar trend in various studies. Most studies applied the AEC system to modulate the tube current and reduce unnecessary radiation exposure to their subjects [16][17][18][19][20]. However, the variation in pitch factor and beam collimation showed different approaches taken by various institutions in utilizing their CT-Scanner.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos anteriores mostram que uma redução semelhante de dose nos órgãos em pacientes adultos utilizando o sistema AEC, chegando a 35%, quando comparado com o uso de uma corrente fixa 16 . A otimização de outros parâmetros, como a utilização de um pitch maior, possibilitou reduções de dose de 44% utilizando o AEC para pacientes adultos 8 .…”
Section: Discussionunclassified